2019
DOI: 10.1055/a-0889-9586
|View full text |Cite
|
Sign up to set email alerts
|

Performance measures for small-bowel endoscopy: a European Society of Gastrointestinal Endoscopy (ESGE) Quality Improvement Initiative

Abstract: The European Society of Gastrointestinal Endoscopy (ESGE) together with the United European Gastroenterology (UEG) recently developed a short list of performance measures for small-bowel endoscopy (i. e. small-bowel capsule endoscopy and device-assisted enteroscopy) with the final goal of providing endoscopy services across Europe with a tool for quality improvement. Six key performance measures for both small-bowel capsule endoscopy and for device-assisted enteroscopy were selected for inclusion, with the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
96
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(109 citation statements)
references
References 123 publications
2
96
0
6
Order By: Relevance
“…To develop standards for high quality in gastrointestinal endoscopy, the European Society of Gastrointestinal Endoscopy (ESGE) has established the ESGE Quality Improvement Committee, which involved several gastrointestinal endoscopy experts to set up quality indicators 9 10 11 12 that, when met, reflect a high-quality examination for different endoscopic procedures. The ESGE Quality Improvement Committee recently appointed a Small Bowel Working Group (ESBWG) to identify a list of performance measures for small bowel endoscopy, including small bowel capsule endoscopy (SBCE) 13 , which has unique technical features. The ESBWG identified six key quality performance measures and four minor performance measures.…”
Section: Introductionmentioning
confidence: 99%
“…To develop standards for high quality in gastrointestinal endoscopy, the European Society of Gastrointestinal Endoscopy (ESGE) has established the ESGE Quality Improvement Committee, which involved several gastrointestinal endoscopy experts to set up quality indicators 9 10 11 12 that, when met, reflect a high-quality examination for different endoscopic procedures. The ESGE Quality Improvement Committee recently appointed a Small Bowel Working Group (ESBWG) to identify a list of performance measures for small bowel endoscopy, including small bowel capsule endoscopy (SBCE) 13 , which has unique technical features. The ESBWG identified six key quality performance measures and four minor performance measures.…”
Section: Introductionmentioning
confidence: 99%
“…Our own data (kappa 0.52 -0.71) confirmed this drawback [3]. Thus, a quality initiative process by the ESGE and UEG recently called for "the development of software for assessment of the quality of smallbowel preparation" [4]. Previous studies based on still frames have demonstrated the high diagnostic performances of handcrafted computerized algorithms in assessing small-bowel cleanliness during capsule endoscopy [11,13].…”
Section: Discussionmentioning
confidence: 68%
“…A consensus standard for technologies in colonoscopy that predict polyp histology (NPV ≥ 90%) was published by the American Society for Gastrointestinal Endoscopy in 2011 30 . We are not aware of an analogous consensus document for WCE but a recently published quality improvement initiative by the European Society for Gastrointestinal Endoscopy recommends a diagnostic yield of at least 50% for all capsule endoscopy readers across indications 31 . Here, we review the literature to date on deep learning in WCE.…”
Section: Artificial Intelligence In Wireless Capsule Endoscopy—an Evomentioning
confidence: 99%